220k views
1 vote
Which shows the equation below written in the form ax^2 + BX + C=0
x+10=3(x - 1)^2


Which shows the equation below written in the form ax^2 + BX + C=0 x+10=3(x - 1)^2 ​-example-1

2 Answers

1 vote

Answer:

Explanation:

User Eatmeimadanish
by
4.6k points
3 votes

Answer:

C

Explanation:

Given

x + 10 = 3(x - 1)² ← expand (x - 1)² using FOIL

x + 10 = 3(x² - 2x + 1) ← distribute

x + 10 = 3x² - 6x + 3 ← subtract x + 10 from both sides

0 = 3x² - 7x - 7 → C

User Maleki
by
4.4k points